Assessing Ship Agency Procedural Management for Marine Waste Handling in Pelindo Marine Service Ports - Ahmad Muzakky; Nisha Desfi Arianti; Tri Mardalena (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study aims to assess the effectiveness of ship agency procedural management for marine waste handling implemented by PT Pelindo Marine Service (PMS) in compliance with international and national maritime environmental standards. Materials and methods: A descriptive qualitative approach was employed utilizing a case study design. Data were collected via structured in-depth interviews with 48 purposively selected participants comprising ship agency officers, port waste management personnel, and ship representatives operating across Pelindo Marine Service branch ports. Triangulated data sources encompassed field observations, documentation analysis of Standard Operating Procedures (SOPs), and official port logbooks. Inductive thematic analysis following the (B & Michael, 1994) framework was applied. Risk assessment conformed to AS/NZS 4360:2004 methodology. Ethical clearance was obtained from the Karimun University Research Ethics Committee (Ref. No. KU-REC/2025/014). Results: Findings reveal that PT PMS has established a five-stage waste disposal procedure aligned with MARPOL 73/78 and ISO 14001:2015; however, critical operational gaps persist. A risk matrix analysis identified 14 hazard categories across five procedural stages, with 6 categorised as high-risk. Facility capacity shortfalls were documented at 67% of branch ports, and crew waste segregation awareness was rated low by 58.3% of respondents. Manual documentation systems contributed to a 23% administrative error rate. Conclusions: PT PMS demonstrates satisfactory regulatory compliance at the procedural framework level, yet significant implementation deficits undermine environmental outcomes. Digital transformation of waste documentation, expansion of port reception facilities, and systematic crew environmental education are urgently recommended to achieve full Green Port certification standards.